2021
DOI: 10.14710/jgi.9.2.136-143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixture powder of black rice (Oryza sativa L indica), red beans (Phaseolus vulgaris L), and moringa leaves (Moringa oleifera L) on blood glucose concentration in hyperglycemic Rats

Abstract: Background: Diabetes mellitus, increased blood glucose or hyperglycemia, is associated with increased oxidative stress and cardiovascular diseases. This condition will further cause carbohydrate and fat metabolism change, resulting in the decreased antioxidant defense system. Black rice, red beans, and moringa leaves contain oleic acid, butyric amino acid, antioxidants, phytic acid, and arginine, which can improve insulin sensitivity, and blood glucose homeostasis.Objective: This study aimed to analyze the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…The results of another study conducted by another study showed that after 28 days of intervention, the mixed powder reduced blood glucose levels in male Wistar rats that were given a glucose load. 21 This is due to the administration of mixed flour in the group containing a high fiber composition, causing satiety quickly compared to the standard feed group. In this study, the mixed powder was used as a flour mixture in the intervention feed, one of the compositions of which was red bean, so that a decrease in fasting blood sugar levels in animal models could be associated with red bean.…”
Section: Results Of Identification Of Titles and Abstracts (N=22)mentioning
confidence: 99%
“…The results of another study conducted by another study showed that after 28 days of intervention, the mixed powder reduced blood glucose levels in male Wistar rats that were given a glucose load. 21 This is due to the administration of mixed flour in the group containing a high fiber composition, causing satiety quickly compared to the standard feed group. In this study, the mixed powder was used as a flour mixture in the intervention feed, one of the compositions of which was red bean, so that a decrease in fasting blood sugar levels in animal models could be associated with red bean.…”
Section: Results Of Identification Of Titles and Abstracts (N=22)mentioning
confidence: 99%
“…Pada penelitian sebelumnya menunjukkan pengaruh pemberian antioksidan yang terkandung dalam beras hitam, kacang merah dan daun kelor (betamelor) pada hewan coba selama 28 hari dapat menurunkan kadar glukosa darah dari 122,69 mg/dL menjadi 97,70 mg/dL dan 123,91 mg/dL menjadi 113,28 mg/dL dengan pemberian pakan betamelor sebanyak 80% dari 5% berat badan (Utama et al, 2021). Penelitian lainnya yang menggunakan Caralluma europaea, yang merupakan tanaman obat tradisional untuk mengobati diabetes mellitus di Maroko.…”
Section: Pendahuluanunclassified